Tool for measuring and analyzing the work route in sample management warehouses - iménez Ramírez, Manuel Arturo J (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2020)
The present paper shows the organization and methods of a work-and-route measurement tool carried out in the warehouse of reactive samples and in the warehouse of samples in custody of an Oil and Gas company in Colombia. This tool is twofold: first is to describe the task carried out and second, is to provide a scheme for the development and improvement processes in the Center of Investigation and development of Oil and Gas Sector, henceforth it is known as CEMIM. The measurement of this work is a research method based on the application of several techniques to determine the activities and content about a defined job, fixing the time in which a qualified worker takes to accomplish the task according to a pre-established standardized performance. Based on this, a work study was carried out at the CEMIM warehouses in accordance to the number of shelves, and the route made by themselves. The results show that when you are considering the route of patterns made by the worker, the analysis of the structured tool provides advantages related to the descrip-tion of the task and the development of methods for the improvement of processes.